Desenvolvimento de sensor de vibração baseado em FBG imersa em elastômero, aplicado em máquinas elétricas - Felix, Adriano (2025)
Vibration monitoring plays a fundamental role in the safety and efficiency of industrial machinery and other equipment. Early fault detection and predictive maintenance are essential to prevent structural damage, reduce operating costs, increase equipment lifespan, and reduce unscheduled downtime. In this context, fiber otic sensors stand out as a technologically advanced solution, offering high sensitivity, immunity to electromagnetic interference, and the ability to operate in adverse environments, among other properties. However, for these sensors to perform reliably, it is necessary to develop suitable encapsulation that protects the optical fiber for the type of application and preserves measurement accuracy. This work presents the development of an encapsulation for fiber otic sensors applied to vibration monitoring in electrical equipment and machines. The study covers the modeling and characterization of the materials used, analyzing their properties and evaluating their impact on the sensitivity of the sensors. The laboratory tests performed demonstrate the effectiveness of the proposed encapsulation and its viability for industrial applications. The need for reliable solutions for industrial monitoring makes this study relevant. Robustly encapsulated fiber otic sensors allow early detection of mechanical and electrical failures, optimizing predictive maintenance and reducing unscheduled downtime. In this way, resource management and operational safety are improved. In addition to its practical impact, the study contributes academically by deepening knowledge about the application of otical sensors in monitoring engineering. The choice of appropriate materials and configurations directly influences the sensor response to vibrations, making a detailed experimental approach essential. In this work, it was demonstrated that the encapsulation of the sensor in silicone elastomer provided a response to dominant frequencies around 30 Hz. Sensitivities of up to 0.8 µɛ in the orthogonal direction and 0.4 µɛ in the longitudinal direction were achieved, fixed to an 1800 rpm electric motor. Tests performed on a vibrating platform (shaker) also indicated a dominant peak at 30 Hz, suggesting that motor vibration is strongly influenced by its rotation frequency. Thus, this work seeks to provide foundations for future research and innovations, aiding in the adoption of this technology by the industry and promoting significant advances in vibration monitoring in complex industrial environments.